2012
DOI: 10.1021/ct200853g
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency of Protein–Ligand Binding Free-Energy Calculations by System Truncation

Abstract: We have studied whether the efficiency of alchemical free-energy calculations with the Bennett acceptance ratio method of protein-ligand binding energies can be improved by simulating only a part of the protein. To this end, we solvated the full protein in a spherical droplet with a radius of 46 Å, surrounded by vacuum. Then, we systematically reduced the size of the droplet and at the same time ignored protein residues that were outside the droplet. Radii of 40 to 15 Å were tested. Ten inhibitors of the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…Typical structures are shown in Figure S1. Our previous studies of both ligand binding and enzyme reaction energies have shown that neutral groups (protein residues or water molecules) outside a distance of 4.5-6.0 Å from the ligand or active site have only a very small influence (<1 kJ/mol) on the binding or reaction energy [64,65,66,67].…”
Section: Dft-d Fep Calculationsmentioning
confidence: 99%
“…Typical structures are shown in Figure S1. Our previous studies of both ligand binding and enzyme reaction energies have shown that neutral groups (protein residues or water molecules) outside a distance of 4.5-6.0 Å from the ligand or active site have only a very small influence (<1 kJ/mol) on the binding or reaction energy [64,65,66,67].…”
Section: Dft-d Fep Calculationsmentioning
confidence: 99%
“…The ligands are shown in Figure . The preparation of the proteins and the ligands has been described before . Functional ferritin is a multimer of almost 100 protein chains, but following earlier investigations, it was modelled as a dimer (the ligand binds at the interface between two subunits) .…”
Section: Methodsmentioning
confidence: 99%
“…However, some groups still use truncated systems, in particular for LIE calculations . Recently, we showed that relative binding free energies calculated by FEP did not change by more than 1.4 kJ/mol if the size of the simulated system was reduced from 46 to 15 Å (from 38,844 to 1480 atoms) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these systems free energy simulations 48 would have provided more reliable estimates of protein−ligand binding affinities and energetics of conformational changes. However, we could not implement them as they are computationally expensive and beyond our reach.…”
Section: Journal Of Chemical Information and Modelingmentioning
confidence: 99%